2018
DOI: 10.1002/brb3.1113
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome and survival following spontaneous intracerebral hemorrhage: A retrospective population‐based study

Abstract: BackgroundAccurate and reliable clinical and radiological predictors of intracerebral hemorrhage (ICH) outcomes are needed to optimize treatment of ICH. The aim of this study was to investigate functional outcome and identify predictors of severe disability or death following ICH.Materials and methodsRetrospective population‐based study of spontaneous ICH. Clinical and radiological data were obtained from electronic medical records, and functional outcome estimated using the modified Rankin Scale (mRS) before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 41 publications
1
25
0
2
Order By: Relevance
“…Our data showed that comorbidities were associated with a higher risk of death and a higher number of comorbidities was associated with a higher risk of death. Increasing CCI score has also previously been reported to be a predictor of severe disability or death within 3 months [13]. The only exception in our data was hypertension, a recorded diagnosis of which was associated with a smaller risk of death.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Our data showed that comorbidities were associated with a higher risk of death and a higher number of comorbidities was associated with a higher risk of death. Increasing CCI score has also previously been reported to be a predictor of severe disability or death within 3 months [13]. The only exception in our data was hypertension, a recorded diagnosis of which was associated with a smaller risk of death.…”
Section: Discussionsupporting
confidence: 68%
“…Indeed, Finland has attained a high level of acute stroke care capability [12]. Previous data have shown that preceding functional disability predicts severe disability or death after ICH [13]. The improved physical and cognitive performance levels of the Finnish elderly and the generally improved life expectance therefore also contribute [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…week was 22.1%, at 3 months 39.2%, and at 12 months 44.9% [27]. Safatli On multivariate analysis, GCS < 9 and NIHSS between 15 -24 were independent predictors of mortality while mass effect and temperature > 37˚C were independent predictors of poor functional recovery after stroke.…”
Section: Discussionmentioning
confidence: 96%
“…ICH accounts for 10-15% of all strokes and is characterized by bleeding inside the brain parenchyma (4,5). Not only does ICH cause death, it causes severe, permanent disability in surviving patients (6). Hematoma formation is the primary cause of adverse outcomes in ICH (7).…”
Section: Introductionmentioning
confidence: 99%